2021
DOI: 10.1111/jvh.13471
|View full text |Cite
|
Sign up to set email alerts
|

Durability of hepatitis B surface antigen seroclearance and subsequent risk for hepatocellular carcinoma: A meta‐analysis

Abstract: Hepatitis B surface antigen (HBsAg) seroclearance is regarded as the ideal endpoint for antiviral treatment. However, reports on the durability of and outcomes after HBsAg seroclearance are few, which has become a focus in clinical practice. This meta‐analysis was performed to evaluate the durability and hepatocellular carcinoma (HCC) incidence after HBsAg seroclearance after treatment cessation. We searched PubMed, Embase, Medline and Web of Science for studies that reported the durability and HCC incidence a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 48 publications
0
32
0
2
Order By: Relevance
“…HBsAg seroclearance or seroconversion has been considered the ideal treatment endpoint for CHB patients ( 1 – 3 ). Some studies showed that the long-term prognosis of patients with CHB could be improved after functional cure ( 4 , 8 , 9 , 12 ). However, relapse still occurs in some patients, and the types of relapse are diverse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HBsAg seroclearance or seroconversion has been considered the ideal treatment endpoint for CHB patients ( 1 – 3 ). Some studies showed that the long-term prognosis of patients with CHB could be improved after functional cure ( 4 , 8 , 9 , 12 ). However, relapse still occurs in some patients, and the types of relapse are diverse.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies related to hepatitis B surface antigen (HBsAg) clearance have increased, but there are still fewer studies related to recurrence after HBsAg clearance. Our previous study and a meta-analysis found that the recurrence rate after functional cure was 6.19%–9.66%, including cases with HBsAg positivity and/or hepatitis B virus (HBV) DNA positivity ( 4 , 5 ). Due to the few large or even sufficient sample relapse cohorts are available for analysis, the effectiveness of retreatment and clinical outcomes after relapse and the correlation between immune function and relapse are even rarer.…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis review paper involving 43,924 patients with chronic hepatitis B found a total recurrence rate after HBsAg clearance of 6.19%, with an average follow-up of 4.74 years. The overall stability was good (38), but there were significant differences between different research populations. We therefore did not include this data.…”
Section: Limitationsmentioning
confidence: 92%
“…73,74 A recent meta-analysis reported that CHB patients had a durable negative HBsAg response after HBsAg seroclearance. 75…”
Section: Durability Of Hbsag Seroclearancementioning
confidence: 99%